Інтеграція та глобалізація освіти в Україні - Тригуб, Інна Петрівна (My University, 2014)
Інтеграція та глобалізація України в європейський освітній простір вимагає від вищої школи значних змін у підготовці майбутніх фахівців. У зв’язку з цим постає проблема проведення чіткої лінії між освітніми та суспільними питаннями. Проаналізовано сучасний стан освіти в Україні. Подано деякі подальші напрямки організації навчального процесу. Ukraine´s integration into European educational space of higher education requires significant changes in the training of future specialists. In connection with this urgency is the problem of independent work, which is the foundation of any education, particularly professional. Prospects for effective solution of urgent problems essentially depend also on the correct structuring and cause-and-effect relationships. Modern state of education was analysed in Ukraine. Further directions of organization of educational process were given.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; інтеграція; глобалізація; освіта; навчальний процес; integration; globalization; education; educational process